The mm-wave compact component of an AGN. Issue 1 (11th May 2018) - Behar, Ehud; Vogel, Stuart; Baldi, Ranieri D; Smith, Krista L; Mushotzky, Richard F
ABSTRACT: mm-wave emission from active galactic nuclei (AGNs) may hold the key to understanding the physical origin of their radio cores. The correlation between radio/mm and X-ray luminosity may suggest a similar physical origin of the two sources. Since synchrotron self-absorption decreases with frequency, mm-waves probe smaller length-scales than cm-waves. We report on 100 GHz (3 mm) observations with the Combined Array for Research in Millimeter-wave Astronomy of 26 AGNs selected from the hard X-ray Swift /Burst Alert Telescope survey. 20/26 targets were detected at 100 GHz down to the 1 mJy (3σ) sensitivity, which corresponds to optically thick synchrotron source sizes of 10 −4 –10 −3 pc. Most sources show a 100 GHz flux excess with respect to the spectral slope extrapolated from low frequencies. This mm spectral component likely originates from smaller scales than the few-GHz emission. The measured mm sources lie roughly around the L mm (100 GHz) ∼10 −4 L X (2–10 keV) relation, similar to a few previously published X-ray selected sources, and hinting perhaps at a common coronal origin.